АN ОVERVIEW ОF THE FUNСTIОN ОF HUMАN RESОURСE MАNАGEMENT IN EMPLОYEE PERFОRMАNСE АND MОTIVАTIОN - Melibаevа Gulxоn Nаzrullаevnа (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The present study shows the crucial relationship that exists between Human Resource Management (HRM) and company success. Specifically, HRM is vital to aligning human resources with strategic objectives. In order to effectively coordinate human resources, HRM must move from administrative duties to a strategic partner role. A motivated workforce and HRM methods are examined in this article, with a focus on hiring, training, and performance reviews. A deeper understanding of employee pleasure is achieved by integrating psychological theories like Maslow's hierarchy and McClelland's wants.